6-Methyl-7,7,9-tripropargyl-7H-1,2,4-triazolo[4,3-b][1,2,4]triazepin-8(9H)-one - Zemama, Redwan Mohamed (International Union of Crystallography, 2009)
The title compound, C(15)H(13)N(5)O, features a triazolyl ring fused with a seven-membered triazepinyl ring; the latter ring adopts a boat conformation (with the propargyl-bearing C atom as the prow and the fused-ring C/N atoms as the stern).